2016
DOI: 10.1007/s12594-016-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

A Neotectonic based Geomorphic Analysis using Remote Sensing Data to Delineate Potential Areas of Hydrocarbon Exploration: Cachar Area, Assam

Abstract: The Assam Arakan fold thrust belt has highly deformed folded units of Tertiary sediments bounded by eastward dipping thrust slices with a convexity towards west. In the Tripura-Cachar region, this folded belt is characterized by the occurrence of wide synclines and narrow anticlines that hosts a number of hydrocarbon producing fields. In the Cachar area of Assam, most of these fields occur in the culmination of anticlinal structures. Other wells drilled in analogous structural settings are found to be dry. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, these structures are associated with a predominantly vertical component of deformation 14 that is imprinted on the surface in the geomorphic elements, especially in sensitive elements like drainage, lineaments and topography 14 . The analysis of these elements is based on the principles discussed in the literaure 15,16 and helps to bring out surface manifestations of the subsurface structures. These surface manifestations are then correlated with the available subsurface data to validate them and establish the subsurface continuity of these interpreted structures.…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these structures are associated with a predominantly vertical component of deformation 14 that is imprinted on the surface in the geomorphic elements, especially in sensitive elements like drainage, lineaments and topography 14 . The analysis of these elements is based on the principles discussed in the literaure 15,16 and helps to bring out surface manifestations of the subsurface structures. These surface manifestations are then correlated with the available subsurface data to validate them and establish the subsurface continuity of these interpreted structures.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Geomorphic highs are delineated from anomalous localized drainage geometries like radial drainages (Figure 4 a) and peripheral/curved drainages (Figure 4 b) 15,16 . These features are used for initial delineation of geomorphic highs in the study area identified from the drainage map of the area.…”
Section: Morphostructural Analysismentioning
confidence: 99%
“…This lineament is also observed to join the Dauki fault northeastward, whereas southwestward it passes over the Barisal-Chandpur subsurface gravity high which is considered to be the manifestation of the continent-ocean crust boundary [1]. The intensity of folding in the region increases from west to east [39] affecting the sequence of rocks ranging in age from upper Cretaceous through Cenozoic.…”
Section: Geological and Stratigraphic Frameworkmentioning
confidence: 89%
“…The belt comprises of thick pile (10-11 km) of sedimentary deposit manifested into a series of NNE-SSW trending, sub-parallel, doubly plunging and highly faulted anticlines and synclines. Major rivers like Barak together with lower-order drainages define a trellis pattern under the influence of alternating synclines and anticlines [39]. The CTFB is bounded on the north by the E-W trending Dauki fault which is assumed to be a thrust associated with right lateral displacement [5,30,34].…”
Section: Geological and Stratigraphic Frameworkmentioning
confidence: 99%
“…The basin is characterized by thick clastic sediments consisting of sandstone and mudstone facies ranging in age from Paleocene to Recent. Several oil and gas fields have been discovered in the basin, which are still under production (Chatterjee et al 2006;Mazumder et al 2016).…”
Section: Study Areamentioning
confidence: 99%